When assistive eye tracking fails: Communicating with a brainstem-stroke patient through the pupillary accommodative response – A case study. (May 2021) - Lorenzo Villalobos, Andres Eduardo; Giusiano, Silvia; Musso, Luca; de'Sperati, Claudio; Riberi, Alessandra; Spalek, Piotr; Calvo, Andrea; Moglia, Cristina; Roatta, Silvestro
Graphical abstract: Highlights: Communication without movement remains an open research and clinical challenge. Voluntary control of pupil size is a novel approach to serve this purpose. A low-cost communication system, based on the pupil accommodative response, is presented. For the first time this approach is successfully tested in a clinical condition. Abstract: Purpose: Poor control of eye movement and coordination may impair the use of eye-trackers for communication in patients affected by severe motor diseases. Recently, the "voluntary" pupil accommodative response (PAR) was suggested as a possible alternative to traditional assistive technology. Aim of this study is to provide a proof of concept of this methodology in a clinical setting. Materials and methods: A low-cost communication system was implemented, which detects the accommodative pupillary constrictions in real time and generates trigger events to drive a commercial scanning-selection interface. As a first implementation, a simple binary yes/no selection interface was designed to be tested with a brainstem stroke patient, unable to use standard communicators based on eye tracking. The patient was instructed to operate the intended selection by switching the focus of attention from a far to a near target, and was then presented with 10 questions with obvious answer. Results: The patient easily understood how to perform the accommodative task. The pupillary constrictions were marked and clearly detectable in spite of the disturbing action of persistent nystagmus. On the first presentation of the device, the patient managed to correctly answer 8 out of 10 questions. Conclusions: The present results provide a proof-of-concept for PAR-based communication in a clinical setting and support its usefulness with patients who, due to impaired control of eye movements, may be unable to use tracking-based devices.